PSII-4 Effects of Late Gestation Supplementation of Vitamin B Complex for Beef Cows. (22nd October 2022) - Ranches, Juliana; Hernandez, Gracia M; Rezende, Aline; Ferreira, Matheus; Bohnert, David
Abstract: The main objective of this study was to evaluate the effects of late gestation and early lactation supplementation of a vitamin B complex on the performance of beef cows and their calves. A total of 48 mature Angus x Hereford cows were randomly assigned (d0) to one of two treatments (1) vitamin (n = 24) or 1) control (n = 24) in early January, allowing for a minimum of 45 days of supplementation before calving and 15 days post-calving. Cows were fed daily with alfalfa hay to the maintenance level. Cows were individually supplemented 3 times weekly (Monday, Wednesday, and Friday) with dried distiller's grains fortified or not with a vitamin B complex. The vitamin B complex was provided at 2/g daily, and therefore was provided at 4.7g/ feeding event. The vitamin B complex contained pantothenic acid (B5), pyridoxine (B6), folic acid (B9), biotin (B7), and cyanocobalamin (B12). Cows and calves were considered the experiment unit for this study and all data were analyzed using the MIXED procedure of SAS (SAS Inst. Inc., Cary, NC, USA). Although all cows were artificially inseminated and pregnancy was checked before the beginning of the study, not all cows enrolled in the study calved within the expected calving range. Therefore, a total of 20 calves were born to cows assigned to control treatment and 19 calves were born to cows assigned to the vitamin treatment. No treatment differences (P ≥ 0.21) were observed for initial (d 0) body weight (BW; 1065 vs.1079 lb, respectively for control and vitamin) or body condition score (BCS; 4.7 vs. 4.8, respectively for control and vitamin) among cows. No treatment differences (P ≥ 0.34) were observed for BW (1168 vs.1161 lb, respectively for control and vitamin) or BCS (5.3 vs. 5.4, respectively for control and vitamin) among cows post-supplementation at turnout (d 90). No differences (P = 0.95) were observed for calf birth weight (81.7 lb); however, calves born to cows supplemented with vitamin tended to be heavier at turnout (P = 0.07; 169.7 vs. 180.5 lb, respectively). These results indicate that supplementation of vitamin B complex to beef cows during late gestation might lead to improved performance of offspring shortly after birth.